DAMPAK REWARDING SEBAGAI UPAYA PENINGKATAN MOTIVASI BELAJAR BAHASA INGGRIS PADA SISWA SMP MUHAMMADIYAH 4 SAMBI SELAMA PANDEMI - Adella Hera Larasati; Yana Febli Suryana; Alfina Dian Arista (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Nowadays, language learning, especially English, encounters many challenges and obstacles in its learning implementation. One example of that obstacle is the student's grades because students lack in deepening the material and vocabulary so that it affects when students work on questions and exams which ultimately has an impact on the final result or the student's own score. The challenge in learning English is how to grow students' motivation to be interested in learning English which is a foreign language for them, plus there are restrictions that exist because of the pandemic that physically and mentally affects students' understanding. These that can be in the form of implementing or providing rewards for students. Rewards can be verbal or non-verbal. Rewarding itself has many positive impacts on the progress or improvement of students' learning motivation which in turn will affect the final grades of the students themselves. Rewarding can be a motivation as well as an appreciation and also a booster for students in learning activities so that the effort given by students will increase because they feel the results of their hard work are well appreciated and in the end there is an increase in student motivation to learn.